Investigating Power Relations in Open Source Software Ecosystems - Farias, Victor Garcia; Santos, Rodrigo; Wiese, Igor; Serebrenik , Alexander; Constantinou, Eleni (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2021)
Context: Relationships within open-source software ecosystems (OSSECO) emerge from collaborations within an ecosystem. Power relations are present in this context whenever an entity has the power of making other entities act as it wants them to act. Therefore, these power relations could affect collaboration within an OSSECO. Objective: This research aims at investigating power relations and providing an understanding of them in OSSECO. A conceptual model will be refined and will represent the power relations and their dynamics. Method: A systematic mapping study was conducted to gather knowledge about power relations from previous studies, and a survey research, considering this knowledge, was conducted with randomly selected npm OSSECO community members to evaluate that knowledge. Next, interviews with selected ecosystem community members will be conducted to identify the types of power relations and their dynamics within an OSSECO. Based on the results from the previous phases, a conceptual model to represent power relations and their dynamics in OSSECO will be refined. Results: The literature review and the survey research with the npm OSSECO community show that, as expected, power relations are present and affect relationships and interactions within an OSSECO. Hierarchy and financial rewards seem to be related to the power relations within the OSSECO. Implications: Identifying power relations that might be present within an OSSECO would enable those who study or are members of the ecosystem's community to understand previous movements and predict future decisions based on the power relations present in their OSSECO.